Typification of the names and taxonomic status of selected vascular plant taxa described by Max Eugen Heinrich Grütter - Pliszko, Artur; Heise, Waldemar (Phytotaxa, 2015)
Max Eugen Heinrich Grütter (30 March 1865–31 March 1897) was a German botanist interested in floristics and taxonomy of vascular plants and mosses (Abromeit 1897). He conducted intensive floristic studies on the territory of the former West and East Prussia, especially in the former West Prussian Province Schwetz (now north-central Poland) where he lived in the small village of Luschkowko (Grütter 1892, 1895a, 1895b, 1895c, 1897). His numerous findings had been frequently cited in “Flora von Ost‑ und Westpreussen” by Abromeit et al. (1898–1940). In 1890–1891, in the course of the floristic expeditions in the former West Prussian Province Schwetz, Grütter found interesting vascular plants which he deemed as new to science. The names of these taxa were validly published in Deutsche botanische Monatsschrift (Grütter 1892).